Observations on Inter-Rater Agreement in Assessing Fusion Activities at Elbow, Wrist and Pelvis by Conventional and Digital X-Ray Films - Aniruddha Das1 , Srimoyee Mukherjee 2 , Arani Majumder3 , Debasis Sarkar4 , Partha Pratim Mukhopadhy (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was designed to measure the inter-rater reliability between two observers in opining andgrading the degree of fusion of the secondary centres of ossification using digital and conventional X ray.Attempt was made to examine whether the digital x-ray is superior to conventional X-ray as regards theinterrater reliability. It was found that The Kappa score ranged from 0.560 to 0.761 for conventional x-rayfilms; whereas it ranged from 0.840 to 0.946 in case of digital x-rays. Interrater agreement was noted tobe near perfect using digital x ray for all the centres of ossification applied in the study .The accuracy ofdigital radiography in age determination by observing the fusion activity at elbow, wrist and pelvis (UsingSchmeling’s staging) will be superior than conventional radiography